Leishmania and leishmaniasis - Kumar, Awanish (SpringerBriefs in Immunology, 2013)
Leishmania-related illnesses remain among the world's deadliest neglected tropical diseases, affecting approximately 12 million people in 88 countries. The mortality rate is substantial, contributing to nearly two million disability-adjusted life years. As more is understood about this parasite and its effects, work toward prevention, control, and treatment continues apace. Leishmania and Leishmaniasis will address the parasite and its attendant disease, which manifests in three syndromes: Visceral (VL), Cutaneous (CL) and Mucocutaneous Leishmaniasis (ML). The morphology and life cycles of the various species will be among the topics addressed in Part One. Part Two will focus on immunology, including host-immune response to Leishmania infection, cross-immunity between the different species and adoptive transfer of immunity. Parts Three and Four will address how Leishmania invade and survive, the clinical features of the disease, and its diagnosis.  Drugs, vaccines and treatment will be thoroughly explored, including experimental models of therapeutics. Leishmania and Leishmaniasis will provide a thorough examination of a parasite, the illnesses it causes and the misery it continues to visit upon large segments of the population.